The Genocide Crime against Kurds in Iraq during the Al-Baath Regime in Iraq and the Responsibility of international community. - Fathi Zeroo Zeroo; Sirwan Latif Haji; Zangin Masiho Awdal (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The research deals with the genocide which is the most dangerous and greatest international crimes, which the Kurdish people in Iraq face it during Al –Baas regime and in particular during Saddam Hussein regim. These crimes and violations led to the killing and disappearance of hundreds of thousands of innocent Kurdish people. Therefore, we will focus on Kurdish genocide in Iraqi Kurdistan and we will discuss the responsibility and procedures of international community which is necessary to punish, limit and eliminate or at least reduce these crime.